HKT sodium and potassium transporters in Arabidopsis thaliana and related halophyte species - Ali, Akhtar (Physiol Plant, 2020)
High salinity induces osmotic stress and often leads to sodium ion‐specific toxicity, with inhibitory effects on physiological, biochemical and developmental pathways. To cope with increased Na(+) in soil water, plants restrict influx, compartmentalize ions into vacuoles, export excess Na(+) from the cell, and distribute ions between the aerial and root organs. In this review, we discuss our current understanding of how high‐affinity K(+) transporters (HKT) contribute to salinity tolerance, focusing on HKT1‐like family members primarily involved in long‐distance transport, and in the recent research in the model plant Arabidopsis and its halophytic counterparts of the Eutrema genus. Functional characterization of the salt overly sensitive (SOS) pathway and HKT1‐type transporters in these species indicate that they utilize similar approaches to deal with salinity, regardless of their tolerance.